Umbilical Cord Mesenchymal Stromal Cells Affected by Gestational Diabetes Mellitus Display Premature Aging and Mitochondrial Dysfunction - Jooyeon Kim; Ying Piao; Youngmi Kim Pak; Dal-Hee Chung; Yu Han; Joon Seok Hong; Eun Jeong Jun; Jae‐Yoon Shim; Jene Choi; Chong Jai Kim (2014)
Human umbilical cord mesenchymal stromal cells (hUC-MSCs) of Wharton's jelly origin undergo adipogenic, osteogenic, and chondrogenic differentiation in vitro. Recent studies have consistently shown their therapeutic potential in various human disease models. However, the biological effects of major pregnancy complications on the cellular properties of hUC-MSCs remain to be studied. In this study, we compared the basic properties of hUC-MSCs obtained from gestational diabetes mellitus (GDM) patients (GDM-UC-MSCs) and normal pregnant women (N-UC-MSCs). Assessments of cumulative cell growth, MSC marker expression, cellular senescence, and mitochondrial function-related gene expression were performed using a cell count assay, senescence-associated β-galactosidase staining, quantitative real-time reverse transcription–polymerase chain reaction, immunoblotting, and cell-based mitochondrial functional assay system. When compared with N-UC-MSCs, GDM-UC-MSCs showed decreased cell growth and earlier cellular senescence with accumulation of p16 and p53, even though they expressed similar levels of CD105, CD90, and CD73 MSC marker proteins. GDM-UC-MSCs also displayed significantly lower osteogenic and adipogenic differentiation potentials than N-UC-MSCs. Furthermore, GDM-UC-MSCs exhibited a low mitochondrial activity and significantly reduced expression of the mitochondrial function regulatory genes ND2, ND9, COX1, PGC-1α, and TFAM. Here, we report intriguing and novel evidence that maternal metabolic derangement during gestation affects the biological properties of fetal cells, which may be a component of fetal programming. Our findings also underscore the importance of the critical assessment of the biological impact of maternal–fetal conditions in biological studies and clinical applications of hUC-MSCs.